REALISASI TEKNOLOGI INFORMASI DAN METAVERSE DI ERA DIGITAL - Peniarsih Peniarsih; Iswandir Iswandir (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
The use of digital information technology or commonly called the internet who already have various platforms such as social media, is wronga medium where users of the platform can search for something data or information, exchanging roles and feedback online. as seen from a variety of popular digital media at this time namely facebook, instagram, twitter, whatsapp, line, bbm, snapchat and some other social media platforms. Hermawan (2009) states that greetings the use of social media can also easily create a forum where individuals communicate and exchange ideas with each other. This will help each personal communicate and comment on various kinds of discussion discussed by people others very easily. Each personal can also build a opinions, emotions and comments through several inside viewpoints exchange ideas with others on social media platforms, that is can allow us to draw conclusions and comment on it spontaneous. In this era, cell phones have turned into smart phones in its role is not only a tool for calling or sending instant messaging, but turned into an advanced technology with additional the latest and revolutionary applications to facilitate delivery information between users. Such rapid progress provide new views that have an impact on the rise of renewal smartphone in this digital era.Â Keywords: Metaverse, Digital , Realisasi, Informacion Teknologi